Detection of miR-210 in formalin fixed human placental tissues using Real Time-PCR / Maimunah Mustakim and Isatou Jagne - Mustakim, Maimunah; Jagne, Isatou (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
MicroRNAs are non-coding regulatory RNAs that are involved in various cell regulation processes. Deregulated expression of miRNAs has been associated with several diseases including preeclampsia. Owing to the huge amount of formalin fixed tissues archived worldwide, this study aims at detecting the presence of miR-210 in formalin fixed placental tissues. Three formalin fixed normal human placentas were used in this study and real time-PCR (RT-PCR) was used as a detection method. Total RNA was extracted from the fixed tissues and miRNA-210 was successfully amplified by RT-PCR. Quantification cycle (Cq) values of three unknown samples were similar; 24.52, 25.06 and 24.32 respectively. Storage of fixed tissues for up to 4 years did not affect the detection of miR-210. In conclusion, RT-PCR is a suitable method in detection of miRNA in formalin fixed tissues including RNAse rich tissues such as placenta. The findings show that archived samples may be used to conduct future studies such as retrospective gene expression studies of miR-210 on both normal and pathological placentas using RT-PCR. This will increase our understanding on the function of miR-210 in the pathogenesis of preeclampsia and pave the way to finding an absolute cure for the disorder.